Executive Preview of Draft Regional Regulations on Industrial Development Planning: Testing the Limits of Executive Authority in Regional Legislation: Executive Preview Rancangan Peraturan Daerah tentang Rencana Pembangunan Industri: Uji Batas Kewenangan Eksekutif dalam Legislasi Daerah - Wardhana, Allan Fatchan Gani; Aditya, Zaka Firma (Universitas Islam Indonesia, 2026)
The obligation of local governments to establish Provincial Industrial Development Plans and Regency/City Industrial Development Plans in the form of Regional Regulations as mandated by Law Number 3 of 2014 concerning Industry requires an evaluation mechanism by the executive before the determination, which is theoretically called an executive preview. The urgency of this research stems from the fact that this mechanism is not regulated in Law Number 12 of 2011 concerning the Formation of Legislation, but only at the Ministerial Regulation level, thus creating legal uncertainty as well as the potential for executive intervention in the legislative function of the Regional People's Representative Council (DPRD). This research formulates two main questions, namely how the limits of executive authority in the practice of executive preview of the formation of Provincial/Regency/City Industrial Development Plan Regulations, and how the regulatory model is in line with the principles of regional autonomy and the function of regional legislation. The method used is normative juridical with a statutory approach, reviewing the Industrial Law, the Regional Government Law, the Law on the Formation of Legislation, and the Minister of Home Affairs Regulation Number 113 of 2018. The results of the study concluded that the executive preview in the preparation of the RPIP/RPIK Regional Regulation is constitutional as long as it is limited to the aspects of formal legality, planning synchronization, and vertical harmonization, not as an instrument of bureaucratic domination over regional policy choices. The need for explicit regulation of the evaluation mechanism for the RPIP/RPIK Regional Regulation draft in Article 245 of the Regional Government Law and the Law on the Formation of Legislation with a recommendatory, participatory, and proportional design.